Groundwater as a source of phosphorus and silicate in an estuarine zone: results from continuous monitoring of nutrients and 222Rn - Oh, Yong Hwa; Kim, Jeonghyun; Kim, Guebuem; Kim, Tae-Hoon (Frontiers in Marine Science, 2023)
The concentrations of 222Rn and dissolved inorganic nutrients in river water at a fixed station of the Nakdong River estuary which has an artificial barrage were continuously measured from October 2014 to May 2015. Monthly benthic 222Rn flux from the river bottom was estimated using a simple mass balance model, taking into account 222Rn sources and sinks. The estimated benthic 222Rn flux shows a significant correlation with groundwater level, suggesting that groundwater level can be used as a representative of the groundwater input. Based on correlation analyses, the concentration of dissolved inorganic nitrogen (DIN) was found to be dependent primarily on river water input. In contrast, the concentrations of dissolved inorganic phosphorus (DIP) and dissolved inorganic silicate (DSi) were predominantly controlled by groundwater input. Our results suggest that groundwater input may be an important source of DIP, especially under P-limited condition, which can affect marine primary production and ecological problems such as eutrophication and algal blooms in the coastal zones.